(untitled) (Herald of Journalism, 2023)
The article focuses on the collection of information from open sources. It analyses those situations where the data does not simply provide a neutral and direct view of the world, but rather has to do with politics and culture, finance and authority. It examines the institutions and infrastructures that underpin data collection, from surveys to statistics, from climate science to social media platforms. The aim of the study is to look at data journalism not only in terms of how things are represented, but also in terms of how it organizes relationships, so that it is not just about creating data stories (through data collection, analysis, visualization and presentation), but also about who and what these stories bring together (including audiences, sources, methods, institutions and social media platforms). Scientific novelty and significance of the work lies in its exploration of handling big data within the field of media communication and journalism in Kazakhstan and other Central Asian countries. It delves into topical areas such as the “platformization” of cross-border investigative journalism, the customization of data alerts and the database of offshore leaks, which are examined in detail. The application of open data in Kyrgyzstan is also discussed in detail. The research strategy and approaches employed in the field of media and communication are also addressed, adding to the overall significance of the study. The article employed applied methods of social research, including quantitative and qualitative approaches. It involved expert analysis of the works of domestic, Western and Russian researchers, along with the establishment of classifications based on the study’s methodology. The results of the study hold significant practical importance for the implementation of information and communication processes within the political system of the state. Scope: media and communications, sociology, etc. The value of the study is that the tools of big data have been considered, focusing on the investigation by journalists of social problems in the region in achieving a sustainable future. The practical significance lies in the development of new approaches for training competent communication professionals and journalists in Kazakhstan and other Central Asian countries. Keywords: big data, data journalism, alert systems, investigative journalism, databases, digitalization, platform.